PENGEMBANGAN INSTRUMEN TES PEMAHAMAN KONSEP MATERI MOMENTUM DAN IMPULS - Bella, Azh Zhahira; Azizahwati, Azizahwati; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The test instrument developed was a multiple choice comprehension test instrument on momentum and impulse material. The purpose of this study was to determine the validity, reliability, level of difficulty, differentiation and deception function of the concept understanding test instrument. This type of research is research and development (R&D) with the Plomp development model. The research instrument used was a concept understanding test instrument and expert validation sheet. Analysis of the data from the test results of this test instrument in class X SMA students showed expert validity with an average score per aspect of 71%, valid questions based on the validity of the items with a total of 12 questions, the reliability of 0.771 in the high category, the items with difficulty difficulty amounting to 4 items and 13 medium difficulty level, 4 items with very good distinguishing power, 3 good categories of distinguishing power, 6 items of distinguishing power, 6 items of distinguishing power with poor criteria questions and 1 item with a negative discrimination value and there are 4 distractors who do not function.Key Words: Concept Understanding, Validity, Reliability, Level of Difficulty, DistinguishingPower, Confusing Functions